GAMBARAN KEPATUHAN PEKERJA BAGIAN PRODUKSI DALAM PENGGUNAAN ALAT PELINDUNG DIRI - karno, karno; Anisa Zulhimah; Djoko Windu P. Irawan; Frida Hendrarinata (Jurnal Higiene Sanitasi, 2022)
Personal Protective Equipment (PPE) is a tool used to prevent or minimize the occurrence of work accidents. Compliance with the use of PPE must be carried out by every worker who will enter the work area. This research was conducted at PT. Syngenta Seed Indonesia with the aim of knowing the description of worker compliance in the use of personal protective equipment at PT. Syngenta Seed Indonesia. This study uses a descriptive type of research. Data collection in this study was obtained by means of observation and questionnaire surveys. The sample of this research is all permanent workers in the production division as many as 24 workers. The variables studied were trust, accept, act, and worker compliance in the use of PPE.The purpose of this study is to determine the level of employee confidence in using PPE. The results of the study indicate that the trust aspect of the workers is mostly in the good category. While the aspects of receiving (accept) and aspects of doing (act) workers are mostly in the less category. From the aspect of believing (belief) as many as 18 (47%) workers are obedient, aspects of accepting (accept) as many as 11 (29%) workers are obedient, and aspects of doing (act) as many as 9 (24%) workers are obedient in the use of PPE so that the value of compliance is obtained. workers by 38 (100%). The conclusion of this study is that workers who have a good level of confidence in the use of PPE do not necessarily manifest in attitudes and actions because it can be caused by several factors, one of which is the convenience of using PPE.